Combination Treatments for Myopia Progression in Children: A Narrative Review - Loreto (Loren) Vaness Tevah Rose (Journal of Clinical & Translational Ophthalmology, 2026)
Despite a growing range of effective monotherapies for childhood myopia control, a subset of children continues to show suboptimal control, prompting interest in combination therapy. This narrative mini-review summarises recent evidence on combining pharmacological, optical, and device-based treatments to slow myopia progression, with emphasis on axial length (AL) as the benchmark of efficacy. The most studied combination is low-dose atropine plus orthokeratology (OK), with multiple studies and meta-analyses reporting greater slowing of AL elongation than OK alone, particularly in younger children and faster progressors. Emerging evidence supports combining low-dose atropine with other refractive interventions, such as defocus-incorporated multisegment (DIMS) and highly aspherical lenslets (HALs), and dual-focus soft contact lenses, although findings vary by study design, atropine dose, and cohort characteristics. Repeated low-level red light (RLRL) therapy combined with OK or DIMS spectacles has also shown improved AL outcomes in some studies, but retinal safety signals and rebound after cessation require careful monitoring. Combination therapy may be most appropriate for fast progressors, notably those with greater than 0.2 mm over 12 months or for inadequate responders to monotherapy, with stepwise escalation guided by AL response, safety, and adherence. Further long-term, randomised trials with standardised endpoints and responder definitions are needed.